he importance of vitamin B12 for neurological and cognitive function: from pregnancy to childhood - Oliveira Caúla Garzone, Emmanuella; Berti Zanella, Priscila (Journal of Health Care, 2021)
Vitamin B12 is important for the central nervous system, being involved in processes such as brain development, neural myelination and cognitive function. Objective: To examine the evidence that links maternal and childhood vitamin B12 with neurological and cognitive development. Materials and methods: Narrative literature review of the last 40 years. The guiding research question for the selection of the studies was: The maternal vitamin B12 status, either during pregnancy or during the breastfeeding period, or food or supplemental B12 intake for pregnant women, breastfeeding woman or offspring, can influence the neurological and cognitive development of these infants and children? Results: The maternal vitamin B12 status during pregnancy and breastfeeding has an influence on the children’s B12 status. During childhood, B12 deficiency correlates with failures in brain development and growth, while data on its influence on children’s cognitive parameters show conflicting results. Vegan or vegetarian women must ensure sufficient intake of vitamin B12 to be able to adequately supply their developing baby as well as they are at greater risk of failure Conclusions: Maternal vitamin B12 status in both pregnancy and breastfeeding is an essential determinant of B12 status in offspring. The heterogeneity of the studies precludes definitive conclusions on the subject